Patterns of Dakwah Communication Among Youth Through Mamaos Cianjuran Culture - Sonjaya, Rasman; Sari, Irma Purnama; Dulwahab, Encep (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
There are various strategies and media for preaching that preachers can carry out or use in their broadcasting activities. You can use local regional culture and arts that are familiar and used by the community for generations. As is often done by the people of the Cianjur area, West Java, who have a tradition of Mamaos Cianjuran songs which are famous outside the area. This research aims to examine the patterns of da'wah communication among Cianjur teenagers who use the Sundanese cultural approach Tembang Mamaos Cianjuran. The method used in this research is descriptive qualitative. From the research results, it was found that there are three patterns of da'wah communication with a cultural approach to the Sundanese song Mamaos Cianjuran, namely: official communication patterns from the regional governments of Cianjur and West Java by making regulations to protect the heritage of the Sundanese song Mamaos Cianjuran; Playing Mamaos Cianjuran songs at various events in the community both formally and informally; Forming a community that teaches Sundanese culture Mamaos Cianjuran. It is hoped that the impact of the research will provide new insights into cultural and arts-based da'wah communication patterns for preachers. Apart from being a medium for spreading Islamic teachings, it can also be an inspiration in maintaining culture and arts which are increasingly being eroded by Western culture.